An oral recombinant vaccine in dogs against Echinococcus granulosus, the causative agent of human hydatid disease: a pilot study. - Anne-Francoise Petavy; Carlos Hormaeche; Samia Lahmar; Hammou Ouhelli; Alejandro Chabalgoity; Thierry Marchal; Samira Azzouz; Fernanda Schreiber; Gabriela Alvite; Marie-Elisabeth Sarciron; Duncan Maskell; Adriana Esteves; et al. (Public Library of Science (PLoS), 2008)
Dogs are the main source of human cystic echinococcosis. An oral vaccine would be an important contribution to control programs in endemic countries. We conducted two parallel experimental trials in Morocco and Tunisia of a new oral vaccine candidate against Echinococcus granulosus in 28 dogs. The vaccine was prepared using two recombinant proteins from adult worms, a tropomyosin (EgTrp) and a fibrillar protein similar to paramyosin (EgA31), cloned and expressed in a live attenuated strain of Salmonella enterica serovar typhimurium.In each country, five dogs were vaccinated with the associated EgA31 and EgTrp; three dogs received only the vector Salmonella; and six dogs were used as different controls. The vaccinated dogs received two oral doses of the vaccine 21 d apart, and were challenged 20 d later with 75,000 living protoscoleces. The controls were challenged under the same conditions. All dogs were sacrificed 26-29 d postchallenge, before the appearance of eggs, for safety reasons.We studied the histological responses to both the vaccine and control at the level of the duodenum, the natural localization of the cestode. Here we show a significant decrease of parasite burden in vaccinated dogs (70% to 80%) and a slower development rate in all remaining worms. The Salmonella vaccine EgA31-EgTrp demonstrated a high efficacy against E. granulosus promoting its potential role in reducing transmission to humans and animals.